1980
DOI: 10.1111/j.2042-3306.1980.tb03401.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma biochemistry in the horse during 3‐day event competition

Abstract: Summary Blood samples were collected from 16 Thoroughbred horses before, during and after the second day of a 3‐day event. Plasma osmolality, concentrations of sodium, potassium, chloride, urea, creatinine, glucose, bilirubin, iron, total protein, albumin, alkaline phosphatase, aspartate aminotransferase, alanine aminotransferase, creatine kinase, calcium, inorganic phosphate, uric acid, cholesterol, triglycerides and non‐esterified fatty acids were measured. Significant differences from pre‐event values were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
31
4
6

Year Published

1995
1995
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 13 publications
11
31
4
6
Order By: Relevance
“…These results are comparable with values previously reported in horses competing in the endurance test of a 3-day event (Rose et al 1980b). Since plasma [Na] is maintained within a narrow range, an increase in plasma [Na] may reflect a relative decrease in TBW, due to a movement of fluid out of the extracellular fluid compartment or dehydration due to a loss of fluid in sweat (Leaf 1962: Rose et al 1980b.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results are comparable with values previously reported in horses competing in the endurance test of a 3-day event (Rose et al 1980b). Since plasma [Na] is maintained within a narrow range, an increase in plasma [Na] may reflect a relative decrease in TBW, due to a movement of fluid out of the extracellular fluid compartment or dehydration due to a loss of fluid in sweat (Leaf 1962: Rose et al 1980b.…”
Section: Discussionsupporting
confidence: 92%
“…and after completion of phase C were used to calculate the net exchangeable cation concentration [CB]. The plasma [Na] measured after phase C was chosen because previous workers have shown that plasma "a] measured after phase C is similar to plasma [Na] measured 30 rnin after phase D (Rose et al 1980b). Body weight was measured 30 rnin after phase D of competition.…”
Section: Measurement Of Plasma Sodium Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Quanto ao comportamento do cálcio em diferentes modalidades esportivas, com menor freqüência observa-se a diminuição durante provas de longa duração e sempre da metade do percurso para o final, conforme reportado em provas de enduro de 110km (Lucke e Hall, 1978), para eventos de três dias (Rose et al, 1980c), em provas de 160 km (Rose et al, 1983b), em provas de 100km (Oosterbaan et al, 1991), e de 76 km no Pantanal de Mato Grosso (Santos et al, 2001). Relatos do aumento do cálcio foram registrados por Snow et al (1982) em prova de enduro de 80km, à velocidade de 16 a 18 km/hora, ao qual atribuiu a marcada hemoconcentração, que mascarou a perda plasmática ocorrida.…”
Section: Resultsunclassified
“…As alterações dos constituintes sangüíneos durante o esforço físico têm sido discutidas por diversos autores no que se refere às mudanças bioquímicas ocorridas em provas de curta distância (Anderson, 1975;Lucke e Hall, 1978;Lucke e Hall, 1980;Rose et al, 1983a;Toledo et al, 2001), às mudanças eletrolíticas nas provas de longas distâncias (Carlson e Mansmann, 1974;Lucke e Hall, 1978;Snow et al, 1982;Rose et al, 1983b;Oosterbaan et al, 1991;Santos et al, 2001;) e aos efeitos hormonais e metabólicos (Rose et al, 1980c;Snow, 1990). Todas as avaliações objetivam proporcionar meios para um treinamento adequado e o diagnóstico precoce das alterações que interferem com o desempenho.…”
Section: Introductionunclassified